Girls on film - Bundy, Clare; Carrig, Lise; Goldman, Sibyl; Pyros, Andrea; McGarity, Shannon; Avirom, Joel; Snyder, Jason (New York HarperPerennial, 1999)
This is not your father's film guide! And you won't find any of this on the Web site!

The creators of the Web site Girls on Film bring you the ultimate video guide, featuring:
-More than 360 recommendations and reviews from every film genre for every movie-watching mood
-Personal stories from the Girls
-Intelligent and fun film chat
-Side-splitting sidebars
Includes filmographies.
Keywords: Motion pictures -- Evaluation